Application of array processing for mobile communications - Ozaman, N. A. B.; Hashim, Nik Mohd Zarifie; Hussin, F.A; A Aziz, Khairul Azha; Salleh, Azahari; Mohamad, Najmiah Radiah (IJARET, 2015)
Digital Signal Processing (DSP) is about a mathematical equation and mathematical operations. It is described by the significations of discrete period, discrete frequency, or supplementary discrete area signals by a order of numbers or signals and the processing of all the signals that related. Digital Signal Processing applications consist of the signal processing for communication. For example is the array processing for the mobile communications. Signal processing is a extensive area of scrutiny that extends from the easiest form of 1-D signal processing to the convoluted form of M-D and array signal processing. This report presents the